The Influence of Cultivation, Storage and Processing Technology on the Nitrate Content in Potato Tubers and Vegetable Crops as the Example of Ecologically and Hygienically Oriented Organic Agricultural Nature Management - Larionov, Maxim Viktorovich; Sargsyan, Karine Shahen; Sayadyan, Hovik Yakhsibek; Margaryan, Varduhi Gurgen; Hunanyan, Surik Aleksandr; Yeritsyan, Sergey Karapet; Jhangiryan, Tatevik Artur; Aleksanyan, Valeri Aleksandr; Hakobjanyan, Inna Lendrush; Galstyan, Meruzhan Haykaram (Journal of Ecohumanism, 2024)
The article presents the results of studies of the influence of organic and mineral fertilizers, as well as storage and processing technologies on the level of nitrates in potatoes, carrots and cabbage. The study demonstrated that in order to obtain the high yield of environmentally friendly vegetable crops, it is necessary to use biohumus at a norm of 8 t/ha or the combination of 6 t/ha biohumus and N35P35K40. This treatment can provide the potato yield of 420-440 c/ha, carrots 223-240 c/ha, cabbage 500-520 c/ha, while not exceeding the maximum allowable concentration (MAC) of nitrates. At a same time, studies have revealed that storage and processing of these vegetables under the required standard conditions can significantly reduce the amount of nitrates contained in the products. The work we have done shows an example of organic farming as the ecological and climatic project for carbon sequestration in soils, bioimprovement and bioprotection of soils, for increasing the yield and hygienic quality of the harvest. When processing the resulting vegetable products, toxic hazards to public health are eliminated and the ecological safety of the environment is ensured. Additional measures are needed to control the application of fertilizers to soils, the quality of agricultural products during collection, storage and processing.